Carbon Emission Assessment and Economic Analysis of Refrigerant Recycling - Wang Yue; Mi Hong; Xu Hong; Zang Jianbin; Wang Haiying (Zhileng xuebao)
China has entered the end of the hydrochlorofluorocarbon (HCFCs) refrigerant phase out, and will soon start to reduce its production and consumption of HFCs simultaneously in 2024. In this study the process of refrigerant recovery and regeneration is investigated. The carbon emission evaluation model for the process of refrigerant recovery and regeneration is constructed based on the life cycle climate performance model LCCP. The economy of the regeneration of refrigerant is analyzed, and the carbon emission and regeneration economy of the automobile air-conditioning refrigerant R134a is calculated using the evaluation model. The results show that the equivalent CO2 emissions can be reduced by approximately 42% by recycling the R134a refrigerant. The economic performance of refrigerant recycling is mainly dependent on the unit price of the refrigerant after regeneration and the wage cost of workers. When the monthly minimum wage standard is used, the price of the refrigerant after purification is more than 11 Yuan/kg (50% of the price of new refrigerant), and the process is profitable within two years.